PENGARUH KONFLIK KEAGENAN TERHADAP CORPORATE GOVERNANCE DAN KINERJA PERUSAHAAN - Wahyu Manuhara Putra (MAKSIMUM, 2011)
AbstractThis study aimed to test whether the Corporate Governance associated the Agent- Conflicts This research Used exploratory principal components analysis and kanonikal analysis on 6 individual governance variables to get the 5 factors representing different dimensions of corporate governance and treasures the agent, conflict firms based on 7 agency conflict proxies used in the literature. Results of analysis found thatCompanies with greater agency conflict has a mechanism for better corporate governance, in particular that the low ownership structure has a high impact on institutional ownership. Overall the result support the theory that the existence and role of corporate governance mechanisms on firm is a function of agencyConflict in the company. Keyword : Agency Conflicts, Corporate Governance, exploratory principal components analysis, kanonikal analysis